Resin-based hard carbon composite material and application thereof in preparation of button type half cell
By regulating the raw material components of the phenolic resin precursor, the conductivity and electrochemical performance of hard carbon composite materials are improved, and the problem of insufficient performance of existing hard carbon materials is solved, and efficient and stable electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411598349.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing hard carbon anode materials have problems such as low efficiency, low specific capacity and cycling performance for the first time, and the chemical composition of biomass precursor materials is inconsistent, making it difficult to ensure the stability of material performance.
By regulating the raw material components of phenolic resin precursors, the intrinsic conductivity of hard carbon is improved, a three-dimensional connected conductive network is built, the electron transmission path is shortened, and the electrochemical performance of composite materials is improved.
The conductivity of resin-based hard carbon composite materials has been significantly improved, and the electrochemical performance has been improved, including the first Coulomb efficiency, specific capacity, magnification and cycling performance, solving the problem of insufficient performance of existing hard carbon materials.
Smart Images

Figure CN119430139A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation and application of negative electrode materials for lithium ion batteries, and specifically relates to a preparation method of a resin-based hard carbon composite material and a new application of the material. Background Art
[0002] With the rapid development of energy storage equipment such as consumer electronics, electric vehicles, and energy storage power stations, the development of energy storage technology has received increasing attention from the industrial and commercial communities. The development of ultra-long life, high energy density, and high-safety energy storage lithium-ion batteries has become the mainstream development trend in the industry. Hard carbon is an amorphous carbon that is difficult to convert into graphite at high temperatures above 2500°C. Due to its special structure with irregular arrangement, it has excellent characteristics such as high energy density, good rate performance and cycle performance. However, hard carbon negative electrode materials have problems such as low initial coulomb efficiency, low specific capacity, and cycle performance, which limit their large-scale commercial application.
[0003] At present, in the field of electrochemical energy storage applications, hard carbon is mainly obtained through pyrolysis of biomass or resin. Biomass-based hard carbon mainly uses biomass such as coconut shells, rice husks, and bamboo as precursors. Before pyrolysis, it is washed, chemically treated, and dried to remove some impurities in the material and improve the consistency of the chemical composition of the precursor material. However, there are differences in the chemical composition of biomass raw materials from different sources, and it is difficult to ensure the consistency of the chemical composition of biomass precursor materials. Resin-based carbon mainly uses various types of high molecular polymers as precursors. Its advantages are mainly reflected in the rich source of raw materials, high purity of raw materials, controllable synthesis, high carbonization yield, easy activation and pore formation, adjustable pore structure, and conducive to heteroatom doping. Among them, phenolic resin-based hard carbon is obtained by condensation of phenolic compounds and aldehyde compounds. By controlling the degree of polymerization of phenolic and aldehyde raw materials and the content of additives, the structure and composition of the material can be precisely controlled.
[0004] Chinese patent application CN201711128166.1 discloses a method for preparing a high-performance silicon-carbon negative electrode material, which is obtained by ball milling and mixing nano-silicon and expanded graphite, and has a high tap density, solving the problem that the silicon-carbon negative electrode material has a thicker electrode sheet and poor electrochemical performance under high surface density conditions. However, the expanded graphite used in this method has a porous structure, so that the electrolyte enters the silicon-carbon negative electrode and reacts with the nano-silicon particles, which affects the battery cycle performance. At the same time, this method cannot solve the problems of electrode pulverization and other problems currently faced by silicon-carbon negative electrodes.
[0005] In addition, Chinese patent application 202311728648.6 discloses a method for preparing a coconut shell-phenolic resin-based silicon-carbon composite material, wherein coconut shell carbon is heated and modified to obtain modified coconut shell carbon; the modified coconut shell carbon and phenolic resin are liquid-phase compounded to obtain a coconut shell carbon-phenolic resin composite material; the coconut shell carbon-phenolic resin composite material is carbonized and activated and then subjected to vapor phase silicon precipitation treatment to obtain the coconut shell-phenolic resin-based silicon-carbon composite material. This method can improve the structural stability and wide temperature range cyclic stability of the prepared material. However, the preparation process of coconut shell carbon not only has environmental pollution problems, but it is also difficult to ensure the stability of the chemical composition and performance of coconut shell carbon.
[0006] The present invention proposes a method for preparing a resin-based hard carbon composite material and a new application of the material. By regulating the components of a phenolic resin precursor raw material, the intrinsic conductivity of the phenolic resin hard carbon is improved, a three-dimensional interconnected conductive network is constructed, the electron transmission path is shortened during the battery charging and discharging process, and the electrochemical performance of the composite material is improved. Summary of the invention
[0007] The purpose of the present invention is to provide a resin-based hard carbon composite material to solve the problems of low first coulombic efficiency, low specific capacity and cycle performance of current hard carbon negative electrode materials, as well as technical difficulties such as differences in chemical composition of biomass raw materials from different sources and difficulty in ensuring the consistency of the chemical composition of biomass precursor materials.
[0008] Another object of the present invention is to provide an application of the above resin-based hard carbon composite material in the preparation of button-type half-cells.
[0009] In order to achieve the above-mentioned object of the present invention, a resin-based hard carbon composite material of the present invention is prepared by the following steps:
[0010] 1) Preparation of mixed solution A: According to the molar ratio of formaldehyde to phenol of (1.4-1.6):1, phenol is melted and then added into the formaldehyde solution, and the mixed solution A is prepared by stirring evenly at a set temperature;
[0011] 2) Preparation of carbon nanotube dispersion slurry B: Carbon nanotube powder and hexadecyltrimethylammonium bromide are dispersed in pure water in a mass ratio of carbon nanotube powder: hexadecyltrimethylammonium bromide: pure water = 1: (0.23-0.33): (17-20), and then ground to obtain carbon nanotube dispersion slurry B;
[0012] 3) Phenolic resin cross-linking and curing: adding carbon nanotube dispersion slurry B to mixed solution A to obtain mixed solution C, adjusting the mixed solution C to pH=8-10 with triethylamine, hexamethylenetetramine, ammonia water and / or sodium hydroxide to prepare a phenolic resin precursor solution; subjecting the prepared phenolic resin precursor solution to a cross-linking and curing reaction at a set temperature, and subjecting the material after the cross-linking and curing reaction to air drying to obtain a phenolic resin curing precursor; the amount of carbon nanotube powder in the mixed solution C accounts for 0.45-1.7% of the mass of phenol;
[0013] 4) Preparation of phenolic resin curing precursor powder: Mechanically grinding the phenolic resin curing precursor obtained in step 2) to a D50 of 40-80 μm to obtain phenolic resin curing precursor powder;
[0014] 5) Preparation of resin-based hard carbon composite materials: The phenolic resin cured precursor powder obtained in step 4) is placed in a tubular furnace, and in a N2 atmosphere, the temperature is raised to 90-110°C at a heating rate of 4-6°C / min and kept warm for 1.3-1.7 hours, raised to 180-220°C and kept warm for 1.8-2.2 hours, raised to 380-420°C and kept warm for 1.8-2.2 hours, and continued to rise to 750-850°C and kept warm for 3.5-4.5 hours, finally obtaining a resin-based hard carbon composite material with an electrical conductivity between 54-100S / cm.
[0015] Preferably, in step 3), the amount of carbon nanotube powder in the mixed solution C accounts for 0.9-1.1% of the mass of phenol.
[0016] Preferably, in step 1), the stirring temperature is set at 70-85°C.
[0017] Preferably, in step 2), the particle size D10 of the added carbon nanotube powder is controlled at 8-12 microns, D50 is controlled at 20-28 microns, and D90 is controlled at 42-50 microns.
[0018] Preferably, in step 3), the temperature set for the cross-linking and curing reaction is 70-90°C, the cross-linking and curing reaction time is 10-15 hours, and the drying temperature is 55-70°C.
[0019] Preferably, in step 1), the stirring temperature is set at 70-85°C; in step 2), the particle size D10 of the added carbon nanotube powder is controlled at 8-12 microns, D50 is controlled at 20-28 microns, and D90 is controlled at 42-50 microns; in step 3), the temperature set for the cross-linking and curing reaction is 70-90°C, the cross-linking and curing reaction time is 10-15 hours, the drying temperature is 55-70°C, and the amount of carbon nanotube powder in the mixed solution C accounts for 0.9-1.1% of the mass of phenol.
[0020] Furthermore, in step 1), the stirring temperature is set at 80°C; in step 3), the cross-linking curing reaction temperature is set at 80°C, the cross-linking curing reaction time is 12 hours, and the drying temperature is 60°C; in step 5), at a heating rate of 5°C / min, the temperature is raised to 100°C and kept warm for 1.5 hours, the temperature is raised to 200°C and kept warm for 2 hours, the temperature is raised to 400°C and kept warm for 2 hours, and the temperature is further raised to 800°C and kept warm for 4 hours.
[0021] In addition, the present invention also provides an application of a resin-based hard carbon composite material in the preparation of a button-type half-cell, which specifically adopts the following steps:
[0022] Preparation of S1 electrode: dissolve an appropriate amount of CMC in water, stir and mix to prepare a CMC glue solution with a concentration of 1.0-1.2%wt; pre-dry and mix the resin-based hard carbon composite material and Super-P powder in a stirring tank in a mass ratio of (40-45): (4.5-5.5): 1: (1.3-1.7) according to the resin-based hard carbon composite material: Super-P: CMC: SBR; transfer the CMC glue solution to a stirring tank for vacuum stirring, add SBR with a concentration of 46-50%wt, continue to stir until the mixture is uniform, and obtain a uniform resin carbon slurry; coat the resin carbon slurry on a copper foil with a thickness of 13-17μm, with a coating thickness of 170-190μm, vacuum dry at 55-70℃, press the tablet at a pressure of 0.008-0.012MPa, and then continue to vacuum dry at 90-110℃ to obtain a resin carbon electrode;
[0023] S2 button half-cell assembly: the resin carbon electrode obtained in step 1) is used as the working electrode, the metal lithium sheet is used as the counter electrode, the polyethylene-polypropylene (PE-PP) is used as the composite diaphragm, and the electrolyte is a solution of lithium hexafluorophosphate (LiPF6) dissolved in an organic solvent [ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1] with a concentration of 1 mol / L, and the button half-cell is assembled in a glove box;
[0024] S3 battery performance test: Use CT3001A blue battery tester to perform charge and discharge tests on button-type half-cells.
[0025] Furthermore, in step S1, the resin-based hard carbon composite material: Super-P: CMC: SBR is in a mass ratio of 85:5:2:3; the copper foil thickness is 15 μm, and the coating thickness is 170 μm; the resin carbon electrode is vacuum dried at 60°C, pressed at a pressure of 0.01 MPa, and then vacuum dried at 100°C to obtain a resin carbon negative electrode.
[0026] Compared with the prior art, the resin-based hard carbon composite material of the present invention and its application in the preparation of button-type half-cells have the following advantages:
[0027] (1) Phenol and formaldehyde are used as raw materials and cross-linked and cured under alkaline conditions to obtain thermosetting phenolic resin. The raw materials are widely available and the preparation process is simple, making it suitable for large-scale industrial production.
[0028] (2) Conductive carbon is introduced at the condensation reaction end of phenol and formaldehyde to form an interconnected conductive network in the composite material, shorten the electron transmission distance between particles, enhance the intrinsic conductivity of the phenolic resin carbon material, greatly improve the conductivity, and significantly reduce the resistivity.
[0029] (3) Studies have shown that the present invention can significantly improve the compressive strength, electrical conductivity and resistivity of the final resin-based hard carbon composite material product by heating and keeping the temperature in four stages during the preparation stage of the resin-based hard carbon composite material.
[0030] (4) The resin-based hard carbon composite material provided in the example of the present invention improves the original intrinsic conductivity of the resin carbon by regulating the material composition. It has the advantages of high capacity, high initial efficiency, high rate and low ash content, and has a very broad application prospect in the field of negative electrode materials for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the SEM image of the carbon nanotube powder used in Example 1.
[0032] Figure 2 This is the SEM image of the resin-based hard carbon composite material prepared in Example 2.
[0033] Figure 3 This is the pore volume and pore size distribution diagram of the phenolic resin-based hard carbon composite material prepared in Example 2.
[0034] Figure 4 This is the charge and discharge curve of the phenolic resin-based hard carbon composite material prepared in Example 2.
[0035] Figure 5 These are the EIS test graphs of the basic group in comparative example 1 and the control group in example 2. DETAILED DESCRIPTION
[0036] To describe the present invention, a phenolic resin-based hard carbon composite material and its application in the preparation of button-type half-cells are further described in detail below in conjunction with the accompanying drawings and embodiments, but this is not intended to limit the present invention.
[0037] Comparative Example 1
[0038] In Comparative Example 1, the resin-based hard carbon material is prepared by the following steps:
[0039] 1) Preparation of phenolic resin precursor solution: 95.1 g of phenol was melted at 60° C., 121.7 g of formaldehyde solution (37 wt.%) was added, the molar ratio of formaldehyde to phenol was 1.5:1, and the mixture was stirred at 80° C. to prepare a mixed solution A (i.e., a phenolic resin precursor solution);
[0040] 2) Phenolic resin cross-linking and curing: adjust the mixed solution A to pH=9 with triethylamine, and perform constant temperature curing reaction at 80°C for 12 hours. After curing, the sample is air-dried at 60°C to obtain a phenolic resin curing precursor;
[0041] 3) Grinding and crushing: mechanically grinding the phenolic resin precursor obtained in step (2) to crush the solidified body particles to a D50 of 40-80 μm, thereby obtaining a phenolic resin solidified precursor powder;
[0042] 4) Preparation of phenolic resin pyrolytic carbon: The phenolic resin curing precursor powder obtained in step (3) is heated to 100°C at a heating rate of 5°C / min in a N2 atmosphere, and then kept warm for 1.5 h, then heated to 200°C and kept warm for 2 h, then heated to 400°C and kept warm for 2 h, and then continued to heat to 800°C and kept warm for 4 h to obtain a resin-based hard carbon material product.
[0043] Example 1
[0044] (1) Preparation of mixed solution A (phenolic resin precursor solution): 95.1 g of phenol was melted at 60° C., 121.7 g of formaldehyde solution (37 wt.%) was added, and the molar ratio of formaldehyde to phenol was 1.5:1. The mixture was stirred at 80° C. to prepare mixed solution A;
[0045] (2) Preparation of carbon nanotube dispersion slurry B: 0.5 g of carbon nanotube powder and cetyltrimethylammonium bromide were weighed and dispersed in pure water in a mass ratio of carbon nanotubes: hexadecyltrimethylammonium bromide: pure water = 5:1.5:93.5, with a ball-to-material ratio of 6:1, a rotation speed of 400 r / min, and ball milling for 6 h to obtain carbon nanotube dispersion slurry B;
[0046] (3) Phenolic resin cross-linking and curing: Add carbon nanotube dispersion slurry B to mixed solution A to obtain mixed solution C, adjust pH to 9 with triethylamine, and perform constant temperature curing reaction at 80° C. for 12 hours. After curing, the sample is dried by forced air at 60° C. to obtain a phenolic resin curing precursor;
[0047] (4) Preparation of phenolic resin curing precursor powder: mechanically grinding the phenolic resin curing precursor, crushing the solidified body particles to a D50 of 40-80 μm, and obtaining phenolic resin curing precursor powder;
[0048] (5) Preparation of resin-based hard carbon composite materials: The phenolic resin curing precursor powder was heated to 100°C at a heating rate of 5°C / min in a N2 atmosphere and kept warm for 1.5 h, then heated to 200°C and kept warm for 2 h, then heated to 400°C and kept warm for 2 h, and then heated to 800°C and kept warm for 4 h to obtain a resin-based hard carbon composite material.
[0049] Example 2
[0050] The difference between Example 2 and Example 1 is that in step (2), the amount of carbon nanotubes added is 1.0 g. Table 1 is a statistical table of pore volumes and pore areas corresponding to different pore diameter segments of the hard carbon composite material of Example 2. The testing instrument is a fully automatic specific surface area and micropore analyzer, the adsorbent is N2, 77.35K, and the pore volume corresponding to pores <10 nm in the hard carbon composite material accounts for about 95% of the total pore volume. A certain amount of micropores and mesoporous structures are beneficial to the infiltration of the electrode material electrolyte and improve the electrochemical performance of the composite material. The SEM image of the resin-based hard carbon composite material prepared in Example 2 is as follows: Figure 2 As shown, after the carbon nanotube powder is pre-dispersed and added, the agglomeration of carbon nanotubes in the composite material is improved, and no carbon nanotube cluster agglomeration phenomenon occurs. Figure 3 This is the pore volume and pore size distribution diagram of the phenolic resin-based hard carbon composite material prepared in Example 2. Figure 4 This is the charge and discharge curve of the phenolic resin-based hard carbon composite material prepared in Example 2. Figure 5 This is the EIS comparison chart of the basic group of comparative example 1 and the control group of embodiment 2. The semicircular arc represents the charge transfer process between the electrode surface and the electrolyte, and its diameter represents the electrochemical impedance caused by the charge transfer process in the electrochemical reaction. The charge transfer resistance decreases after adding carbon nanotube slurry, indicating that the conductivity of the hard carbon composite material is significantly improved compared with the hard carbon material of the basic group.
[0051] Table 1 Pore size distribution of hard carbon composite material in Example 2
[0052]
[0053] Example 3
[0054] The difference between Example 3 and Example 1 is that in step (2), the amount of carbon nanotubes added is 1.5 g.
[0055] Comparative Example 2
[0056] (1) Preparation of phenolic resin precursor solution: 95.1 g of phenol was melted at 60° C., 121.7 g of formaldehyde solution (37 wt.%) was added, and the molar ratio of formaldehyde to phenol was 1.5:1. The mixture was stirred at 80° C. to prepare a mixed solution A;
[0057] (2) Preparation of Super-P slurry: 0.5 g of Super-P powder and cetyl trimethyl ammonium bromide were dispersed in pure water in a mass ratio of Super-P: cetyl trimethyl ammonium bromide: pure water = 5:1.5:93.5, with a ball-to-material ratio of 6:1, a rotation speed of 400 r / min, and ball milling for 6 h to obtain Super-P dispersed slurry B;
[0058] (3) Phenolic resin cross-linking and curing: Super-P dispersion slurry B is added to the mixed solution A to obtain a mixed solution C, and the pH is adjusted to 9 by triethylamine. The reaction is carried out at a constant temperature of 80°C for 12 hours. After curing, the sample is dried by forced air at a drying temperature of 60°C to obtain a phenolic resin curing precursor;
[0059] (4) Preparation of phenolic resin precursor powder: mechanically grinding the cross-linked and cured phenolic resin precursor to crush the solidified particles to a D50 of 40-80 μm to obtain phenolic resin precursor powder;
[0060] (5) Preparation of phenolic resin pyrolytic carbon: In a N2 atmosphere, the phenolic resin precursor powder was heated to 100°C at a heating rate of 5°C / min and kept warm for 1.5 h, then heated to 200°C and kept warm for 2 h, then heated to 400°C and kept warm for 2 h, and then heated to 800°C and kept warm for 4 h to obtain a resin-based hard carbon composite material.
[0061] Comparative Example 3
[0062] (1) Preparation of phenolic resin precursor solution: 95.1 g of phenol was melted at 60° C., 121.7 g of formaldehyde solution (37 wt.%) was added, and the molar ratio of formaldehyde to phenol was 1.5:1. The mixture was stirred at 80° C. to prepare a mixed solution A;
[0063] (2) Preparation of acetylene black slurry: according to the mass ratio of acetylene black: hexadecyltrimethylammonium bromide: pure water = 5:1.5:93.5, weigh 0.5g of acetylene black powder and hexadecyltrimethylammonium bromide and disperse them in pure water, with a ball-to-material ratio of 6:1, a rotation speed of 400r / min, and ball milling for 6h to obtain acetylene black dispersion slurry B;
[0064] (3) Phenolic resin cross-linking and curing: acetylene black dispersion slurry B is added to the mixed solution A to obtain a mixed solution C, and the pH is adjusted to 9 by using triethylamine. The mixture is cured at 80° C. for 12 hours. After curing, the sample is dried by forced air at 60° C. to obtain a phenolic resin curing precursor;
[0065] (4) Preparation of phenolic resin precursor powder: mechanically grinding the cross-linked and cured phenolic resin precursor to crush the solidified particles to a D50 of 40-80 μm to obtain phenolic resin precursor powder;
[0066] (5) Preparation of phenolic resin pyrolytic carbon: In a N2 atmosphere, the phenolic resin precursor powder was heated to 100°C at a heating rate of 5°C / min and kept warm for 1.5 h, then heated to 200°C and kept warm for 2 h, then heated to 400°C and kept warm for 2 h, and then heated to 800°C and kept warm for 4 h to obtain a resin-based hard carbon composite material.
[0067] Application Example 1
[0068] The application of a resin-based hard carbon composite material in the preparation of a button-type half-cell of the present invention adopts the following steps:
[0069] Preparation of S1 electrode: Dissolve 0.2g of CMC in 17mL of water, stir magnetically for 10h, and mix to prepare CMC glue with a concentration of 1.0-1.2%wt; Place the resin-based hard carbon composite material products and Super-P prepared in Examples 1 and 2 in a vacuum drying oven and dry at 100°C for 10h. Resin-based hard carbon composite material: Super-P: CMC: SBR according to the mass ratio of 85:10:2:3, the resin-based hard carbon composite material and Super-P powder are pre-dry mixed in a stirring tank; the CMC glue is transferred to the stirring tank, vacuum stirred at a speed of 200r / min, SBR with a concentration of 48%wt is added, and stirring is continued until the mixture is uniform to obtain a uniform resin carbon slurry; the resin carbon slurry is coated on a copper foil with a thickness of 15μm, and the coating thickness is 180μm. After vacuum drying at 60°C for 2h, it is pressed at a pressure of 0.01MPa, and then vacuum dried at 100°C for 2h to obtain a resin carbon pole piece sample;
[0070] S2 button half-cell assembly: the resin carbon electrode sample prepared in step 1) is used as the working electrode, the metal lithium sheet is used as the counter electrode, the polyethylene-polypropylene (PE-PP) is used as the composite diaphragm, and the electrolyte is a solution of lithium hexafluorophosphate (LiPF6) dissolved in an organic solvent [ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1] with a concentration of 1 mol / L, and the button half-cell is assembled in a glove box;
[0071] S3 battery performance test: Use CT3001A blue battery tester to perform charge and discharge tests on button-type half-cells.
[0072] Table 2 shows the test results of the electrical conductivity of the hard carbon composite material powders prepared in Examples 1-3 and Comparative Examples 1-3.
[0073] Table 2 Electrical conductivity test of resin-based hard carbon material powder prepared in Examples 1-3 and Comparative Examples 1-3
[0074]
[0075] It can be seen from the results in Table 2 that, compared with Comparative Examples 1, 2, and 3, the addition of carbon nanotube powder greatly increased the conductivity and significantly reduced the resistivity, achieving unexpected technical effects. Among them, the hard carbon composite material powder prepared in Example 2 has the highest conductivity, that is, the effect of adding carbon nanotubes after pre-dispersion is the best, giving full play to the unique one-dimensional linear structure of carbon nanotubes, and a more complete electronic conductive network can be constructed at the same mass addition amount.
[0076] Table 3 shows the electrochemical performance test results of the hard carbon composite material powders prepared in Examples 1-3 and Comparative Examples 1-3. According to the test results of Examples 1-3, the electrochemical performance of Example 2 is significantly improved, the carbon nanotube and resin composite material has higher conductivity, the first coulomb efficiency of the hard carbon composite material is improved, and the composite material rate and cycle performance are improved.
[0077] Table 3 Electrochemical properties of hard carbon composite material powders prepared in Examples 1-3 and Comparative Examples 1-3
[0078]
[0079] It can be seen from the results in Table 3 that the first coulombic efficiency, 0.1C first discharge specific capacity, 5C discharge capacity retention rate, and 50-cycle capacity retention rate of the hard carbon composite material prepared after adding carbon nanotube powder are all significantly improved.
Claims
1. A resin-based hard carbon composite material, characterized in that Prepared by the following steps: 1) Preparation of mixed solution A: According to the molar ratio of formaldehyde to phenol of (1.4-1.6):1, phenol is melted and then added into the formaldehyde solution, and the mixed solution A is prepared by stirring evenly at a set temperature; 2) Preparation of carbon nanotube dispersion slurry B: Carbon nanotube powder and hexadecyltrimethylammonium bromide are dispersed in pure water in a mass ratio of carbon nanotube powder: hexadecyltrimethylammonium bromide: pure water = 1: (0.23-0.33): (17-20), and then ground to obtain carbon nanotube dispersion slurry B; 3) Phenolic resin cross-linking and curing: adding carbon nanotube dispersion slurry B to mixed solution A to obtain mixed solution C, adjusting the mixed solution C to pH=8-10 with triethylamine, hexamethylenetetramine, ammonia water and / or sodium hydroxide to prepare a phenolic resin precursor solution; subjecting the prepared phenolic resin precursor solution to a cross-linking and curing reaction at a set temperature, and subjecting the material after the cross-linking and curing reaction to air drying to obtain a phenolic resin curing precursor; the amount of carbon nanotube powder in the mixed solution C accounts for 0.45-1.7% of the mass of phenol; 4) Preparation of phenolic resin curing precursor powder: Mechanically grinding the phenolic resin curing precursor obtained in step 2) to a D50 of 40-80 μm to obtain phenolic resin curing precursor powder; 5) Preparation of resin-based hard carbon composite materials: The phenolic resin cured precursor powder obtained in step 4) is placed in a tubular furnace, and in a N2 atmosphere, the temperature is raised to 90-110°C at a heating rate of 4-6°C / min and kept warm for 1.3-1.7 hours, raised to 180-220°C and kept warm for 1.8-2.2 hours, raised to 380-420°C and kept warm for 1.8-2.2 hours, and continued to rise to 750-850°C and kept warm for 3.5-4.5 hours, finally obtaining a resin-based hard carbon composite material with an electrical conductivity between 54-100S / cm.
2. A resin-based hard carbon composite material according to claim 1, characterized in that: In step 3), the amount of carbon nanotube powder in the mixed solution C accounts for 0.9-1.1% of the mass of phenol.
3. The resin-based hard carbon composite material according to claim 1, characterized in that: In step 1), the stirring temperature is set at 70-85°C.
4. The resin-based hard carbon composite material according to claim 1, characterized in that: In step 2), the particle size D10 of the added carbon nanotube powder is controlled at 8-12 microns, D50 is controlled at 20-28 microns, and D90 is controlled at 42-50 microns.
5. The resin-based hard carbon composite material according to claim 1, characterized in that: In step 3), the temperature set for the cross-linking and curing reaction is 70-90°C, the cross-linking and curing reaction time is 10-15 hours, and the drying temperature is 55-70°C.
6. The resin-based hard carbon composite material according to claim 1, characterized in that: In step 1), the stirring temperature is set at 70-85°C; in step 2), the particle size D10 of the added carbon nanotube powder is controlled at 8-12 microns, D50 is controlled at 20-28 microns, and D90 is controlled at 42-50 microns; in step 3), the temperature set for the cross-linking and curing reaction is 70-90°C, the cross-linking and curing reaction time is 10-15 hours, the drying temperature is 55-70°C, and the amount of carbon nanotube powder in the mixed solution C accounts for 0.9-1.1% of the mass of phenol.
7. A resin-based hard carbon composite material according to claim 6, characterized in that: In step 1), the stirring temperature is set to 80°C; in step 3), the cross-linking curing reaction temperature is set to 80°C, the cross-linking curing reaction time is 12 hours, and the drying temperature is 60°C; in step 5), at a heating rate of 5°C / min, the temperature is raised to 100°C and kept warm for 1.5 hours, the temperature is raised to 200°C and kept warm for 2 hours, the temperature is raised to 400°C and kept warm for 2 hours, and the temperature is further raised to 800°C and kept warm for 4 hours.
8. Use of a resin-based hard carbon composite material as claimed in claim 1, 2, 3, 4, 5, 6 or 7 in the preparation of a button-type half-cell, characterized in that Use the following steps: Preparation of S1 electrode: dissolve an appropriate amount of CMC in water, stir and mix to prepare a CMC glue solution with a concentration of 1.0-1.2%wt; pre-dry and mix the resin-based hard carbon composite material and Super-P powder in a stirring tank in a mass ratio of (40-45): (4.5-5.5): 1: (1.3-1.7) according to the resin-based hard carbon composite material: Super-P: CMC: SBR; transfer the CMC glue solution to a stirring tank for vacuum stirring, add SBR with a concentration of 46-50%wt, continue to stir until the mixture is uniform, and obtain a uniform resin carbon slurry; coat the resin carbon slurry on a copper foil with a thickness of 13-17μm, with a coating thickness of 170-190μm, vacuum dry at 55-70℃, press the tablet at a pressure of 0.008-0.012MPa, and then continue to vacuum dry at 90-110℃ to obtain a resin carbon electrode; S2 button half-cell assembly: the resin carbon electrode obtained in step 1) is used as the working electrode, the metal lithium sheet is used as the counter electrode, the polyethylene-polypropylene (PE-PP) is used as the composite diaphragm, and the electrolyte is a solution of lithium hexafluorophosphate (LiPF6) dissolved in an organic solvent [ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1] with a concentration of 1 mol / L, and the button half-cell is assembled in a glove box; S3 battery performance test: Use CT3001A blue battery tester to perform charge and discharge tests on button-type half-cells.
9. The use of a resin-based hard carbon composite material in the preparation of a button-type half-cell according to claim 8, characterized in that: In step S1, the resin-based hard carbon composite material: Super-P: CMC: SBR is in a mass ratio of 85:5:2:3; the copper foil thickness is 15 μm, and the coating thickness is 170 μm; The resin carbon electrode sheet was vacuum dried at 60°C, pressed at a pressure of 0.01MPa, and then vacuum dried at 100°C to obtain a resin carbon negative electrode sheet.
Citation Information
Patent Citations
A high-performance silicon-carbon anode material and its preparation method
CN107785560B
Coconut shell-phenolic resin-based silicon-carbon composite material and preparation and application thereof
CN117727918A
Cited By
Carbon nanotube modified phenolic resin and application thereof in porous carbon and silicon carbon
CN121045734A